ER–plastid contact sites as molecular crossroads for plastid lipid biosynthesis - Carolina Huercano; Miriam Moya-Barrientos; Oliver Cuevas; Victoria Sanchez-Vera; Noemi Ruiz-Lopez (BMC Biology)
Abstract Membrane contact sites are specialized regions where organelle membranes are in close proximity, enabling lipid transfer while preserving membrane identity. In plants, ER‒chloroplast contact sites are critical for maintaining glycerolipid homeostasis. This review examines the lipid-modifying and lipid-transfer proteins/complexes involved in these processes. Key proteins at these sites, including components of the TGD and VAP27‒ORP2A complexes, as well as Sec14 proteins, facilitate lipid exchange. Additionally, the roles of lipid-modifying proteins at these contact sites are discussed. Despite significant progress, further research is needed to identify additional proteins, investigate ER‒chloroplast dynamics under stress and explore ER contact sites in non-chloroplast plastids.